Health worker preferences for community-based health insurance payment mechanisms: a discrete choice experiment - Robyn Paul; Bärnighausen Till; Souares Aurélia; Savadogo Germain; Bicaba Brice; Sié Ali; Sauerborn Rainer (BMC, 2012)
Abstract Background In 2004, a community-based health insurance scheme (CBI) was introduced in Nouna health district, Burkina Faso. Since its inception, coverage has remained low and dropout rates high. One important reason for low coverage and high dropout is that health workers do not support the CBI scheme because they are dissatisfied with the provider payment mechanism of the CBI. Methods A discrete choice experiment (DCE) was used to examine CBI provider payment attributes that influence health workers' stated preferences for payment mechanisms. The DCE was conducted among 176 health workers employed at one of the 34 primary care facilities or the district hospital in Nouna health district. Conditional logit models with main effects and interactions terms were used for analysis. Results Reimbursement of service fees (adjusted odds ratio (aOR) 1.49, p < 0.001) and CBI contributions for medical supplies and equipment (aOR 1.47, p < 0.001) had the strongest effect on whether the health workers chose a given provider payment mechanism. The odds of selecting a payment mechanism decreased significantly if the mechanism included (i) results-based financing (RBF) payments made through the local health management team (instead of directly to the health workers (aOR 0.86, p < 0.001)) or (ii) RBF payments based on CBI coverage achieved in the health worker's facility relative to the coverage achieved at other facilities (instead of payments based on the numbers of individuals or households enrolled at the health worker's facility (aOR 0.86, p < 0.001)). Conclusions Provider payment mechanisms can crucially determine CBI performance. Based on the results from this DCE, revised CBI payment mechanisms were introduced in Nouna health district in January 2011, taking into consideration health worker preferences on how they are paid.